Establishing the dose of memory support to improve patient memory for treatment and treatment outcome. (September 2020) - Lee, Jason Y.; Dong, Lu; Gumport, Nicole B.; Harvey, Allison G.
Abstract: Background and objectives: Patient memory for the contents of treatment sessions is poor and this is associated with worse treatment outcome. Preliminary findings indicate that treatment provider use of memory support can be helpful in enhancing patient memory for treatment and improving outcome. The development of a novel Memory Support Intervention is currently underway. A key step in this process is to establish the dose of memory support that treatment providers deliver in treatment-as-usual, as well as the optimal dose of memory support needed to maximize patient memory for treatment points and outcomes. Methods: Forty-two adults with major depressive disorder (MDD) were randomized to receive either cognitive therapy plus memory support (CS + Memory Support; n  = 22) or cognitive therapy as-usual (CT-as-usual; n  = 20). Patients completed a free recall of treatment points task at post-treatment. Outcome measures were administered at baseline and post-treatment. Results: Treatment providers delivering CT-as-usual used, on average, 8.39 instances of memory support and 3.40 different types of memory support per session. Receiver Operating Characteristics (ROC) analyses using the combined sample indicate that 12.45 instances of memory support and 3.88 to 4.13 different types of memory support are needed to maximize patient recall and functional outcome. Limitations: Dosing recommendations were established using a limited sample of participants receiving cognitive therapy for MDD. Conclusions: Treatment providers appear to deliver a suboptimal amount of memory support. Delivering the optimal dose of memory support could improve treatment outcome. Highlights: Patient memory for treatment contents is poor and this is associated with worse outcome. Memory support has been demonstrated to improve patient memory for treatment. Treatment providers deliver a suboptimal amount of memory support. Delivering the optimal dose of memory support could improve treatment outcome.